Pemilihan supplier kayu kayu pada cv integritas mulia bersama untuk menentukan prioritas supplier kayu bagi perusahaan dengan menggunakan metode analytic network process(ANP) - Dodi Saktyo Arzaqi; Febri Nugroho Mujiraharjo; Noor Nailie Azzat (Universitas Krisnadwipayana, 2026)
This research is motivated by the problem faced by CVIntegritas Mulia Bersama, which failed to achieveproduction targets due to late deliveries from severalsuppliers. The company wanted to determine whichcriteria were prioritized in supplier selection.Decision-making is crucial for any company, asdetermining priorities is crucial for improving thequality and product quality of a company. Oneexample is improving wood quality, price, supplierservice, and chair delivery. The Analytic NetworkProcess (ANP) method is a crucial factor in decision-making, enabling the company to systematicallyidentify dependencies and provide feedback. Datacollection in this study involved interviews andquestionnaires directed at the production manager,production head, and production supervisor. The ANPcalculation in this study used Super Decisions dataprocessing software, which uses the ANP method. Thesupplier priority ranking was determined by CompanyB with a weight of 0.60082, Company C with a weightof 0.45246, and Company A with a weight of 0.41737.From these results, it can be concluded that thepriority order for selecting the best supplier based onwood quality, price, supplier service, and chairdelivery is Company B, as it has the most ideal value.